Mineral inadequacy of oral diets offered to patients in a Brazilian hospital - D. C. F. Moreira (Nutrición Hospitalaria, 2012)
Introduction: While enteral diets for hospitalized patients normally follow nutrient composition guidelines, more than 90% of hospitalized patients receive oral diets with unknown mineral composition. Objective: To evaluate the mineral contents and adequacy of three types of oral diets (regular, blend and soft) and complementary snacks offered to patients of a Brazilian hospital. Methods: The amount of minerals was determined in two nonconsecutive days in duplicate samples of breakfast, collation, lunch, snack, dinner, supper and a complementary snack meal. Dietary Reference Intakes (DRIs) were used to determine the adequacy of the daily amounts served to patients. Results and discussion: The regular diet met the RDA (Recommended Dietary Allowances) requirements only for Mn, P and Se, while the blend diet was deficient in Ca, K and Mg, and the soft diet met RDA requirements only for P and Zn. Iron was below the RDA requirement in all diets for women in fertile age, and Na was above the safe limit of intake (UL) in all the diets. The use of complementary snack was effective in meeting RDA requirements for Cu in the regular diet, and Mn and Se in the soft diet, but promoted overconsumption of Na. Conclusions: Evident nutritional imbalances have been detected at a key interphase between nutrition and public health services, but a solution does not appear to be insurmountable. A permanent nutritional evaluation of hospital oral diets should be an integral part of routine health care in order to speed the recovery of the hospitalized patient and dispel eventual risks due to critical mineral imbalances.